Indonesian Government Efforts to Improve Early Childhood Education: A Balanced Quality Perspective - Sufa, Feri Faila; Setiawan, M. Hery Yuli; Irmade, Oka (International Journal of Psychosocial Rehabilitation, 2020)
Early childhood education (ECE) is considered to be essential and strategic in the process of human resource development. It has precisely identical terms in Indonesian perspective. Based on the strategic plan for early childhood education and education community, it is necessary to increase ECE’s access which needs to be balanced with its quality. The purpose of this study is to find out how the efforts made by the government to improve the quality of ECE. A qualitative approach is carried out using interviews, observation and documentation in Solo Raya area to see how ECE institutions improve their quality. The results show that in gaining the quality of the institution, it was conducted through internal and external ways. ECE's internal quality development was done through quality mapping by the education office. In addition, the external quality improvement was taken by meeting the standard from National Accreditation Council for Early Childhood Education and Non-formal Education.